Transcriptome profile analysis of flowering molecular processes of early flowering trifoliate orange mutant and the wild-type [Poncirus trifoliata (L.) Raf.] by massively parallel signature sequencing - Zhang, Jin-Zhi (BioMed Central, 2011)
BACKGROUND: After several years in the juvenile phase, trees undergo flowering transition to become mature (florally competent) trees. This transition depends on the balanced expression of a complex network of genes that is regulated by both endogenous and environmental factors. However, relatively little is known about the molecular processes regulating flowering transition in woody plants compared with herbaceous plants. RESULTS: Comparative transcript profiling of spring shoots after self-pruning was performed on a spontaneously early flowering trifoliate orange mutant (precocious trifoliate orange, Poncirus trifoliata) with a short juvenile phase and the wild-type (WT) tree by using massively parallel signature sequencing (MPSS). A total of 16,564,500 and 16,235,952 high quality reads were obtained for the WT and the mutant (MT), respectively. Interpretation of the MPSS signatures revealed that the total number of transcribed genes in the MT (31,468) was larger than in the WT (29,864), suggesting that newly initiated transcription occurs in the MT. Further comparison of the transcripts revealed that 2735 genes had more than twofold expression difference in the MT compared with the WT. In addition, we identified 110 citrus flowering-time genes homologous with known elements of flowering-time pathways through sequencing and bioinformatics analysis. These genes are highly conserved in citrus and other species, suggesting that the functions of the related proteins in controlling reproductive development may be conserved as well. CONCLUSION: Our results provide a foundation for comparative gene expression studies between WT and precocious trifoliate orange. Additionally, a number of candidate genes required for the early flowering process of precocious trifoliate orange were identified. These results provide new insight into the molecular processes regulating flowering time in citrus.